2011
DOI: 10.1037/a0021660
|View full text |Cite
|
Sign up to set email alerts
|

The joint structure of DSM-IV Axis I and Axis II disorders.

Abstract: The Diagnostic and Statistical Manual (4th ed. [DSM–IV]; American Psychiatric Association, 1994) distinction between clinical disorders on Axis I and personality disorders on Axis II has become increasingly controversial. Although substantial comorbidity between axes has been demonstrated, the structure of the liability factors underlying these two groups of disorders is poorly understood. The aim of this study was to determine the latent factor structure of a broad set of common Axis I disorders and all Axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
156
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(180 citation statements)
references
References 83 publications
19
156
1
4
Order By: Relevance
“…In this model, antisocial and borderline personality disorders comprise a single factor representing externalizing behavior, while histrionic and narcissistic personality disorders represent another factor representing attention-seeking grandiosity. This is in concordance with some studies that have found narcissistic and histrionic personality disorder to load onto a different factor than antisocial personality disorder (e.g., Røysamb et al, 2011). Also, some studies have found that traits characterizing narcissistic and histrionic personality disorders (i.e., grandiosity, attention-seeking) and antisocial personality (i.e., impulsivity, irresponsibility) load onto separate factors at the lowest level of the hierarchy (e.g., Wright & Simms, 2014).…”
Section: Higher-order Modelssupporting
confidence: 80%
See 2 more Smart Citations
“…In this model, antisocial and borderline personality disorders comprise a single factor representing externalizing behavior, while histrionic and narcissistic personality disorders represent another factor representing attention-seeking grandiosity. This is in concordance with some studies that have found narcissistic and histrionic personality disorder to load onto a different factor than antisocial personality disorder (e.g., Røysamb et al, 2011). Also, some studies have found that traits characterizing narcissistic and histrionic personality disorders (i.e., grandiosity, attention-seeking) and antisocial personality (i.e., impulsivity, irresponsibility) load onto separate factors at the lowest level of the hierarchy (e.g., Wright & Simms, 2014).…”
Section: Higher-order Modelssupporting
confidence: 80%
“…As mentioned above, studies of personality pathology often split the internalizing factor into negative affect and detachment factors, with the latter factor describing interpersonal difficulty. Similar factors labeled pathological introversion (Markon, 2010) and anhedonic introversion (Røysamb et al, 2011) have been supported in other studies. Based on these findings, the third factor includes dependent and avoidant personality disorders and social anxiety disorder; this factor was labeled interpersonal sensitivity (see Figure 2).…”
Section: Higher-order Modelssupporting
confidence: 71%
See 1 more Smart Citation
“…In order to investigate the broad construct of internalizing disorders, the following lifetime disorders were selected for the present study: major depressive disorder, dysthymia, generalized anxiety disorder, social phobia, panic disorder, and agoraphobia. As these disorders are strongly interrelated (Hettema et al, 2006;Krueger & Markon, 2006;Røysamb et al, 2011), a dichotomized index (no lifetime internalizing disorder vs. any lifetime internalizing disorder) was generated based on the specific diagnostic data.…”
Section: Diagnostic Interview the Norwegian Version Of The Computerimentioning
confidence: 99%
“…The SIDP-IV is a comprehensive semi-structured diagnostic interview for DSM-IV personality disorder (Axis II) diagnoses. The SIDP-IV has been used in numerous studies in different countries, including Norway (3,11,33). It covers 14 DSM-IV Axis II diagnoses as well as conduct disorder as a separate Axis I disorder.…”
Section: Methodsmentioning
confidence: 99%